Ability 50 Meters Sprint In Terms Of The Performance Of Leg Length And Weight Of SDS Bakau Estate Students - Jusran S.; Hasrudin Hasrudin; Hasniah Hasniah; Sitti Maifa; Andi Nurfaida P.; Faisal Batennie (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the performance of leg length and body weight in the ability to sprint 50 meters of SDS Bakau Estate students. This research is a quantitative descriptive study with two independent variables, namely leg length and body weight with one dependent variable sprint of 50 meters. The number of samples in this study is limited to 30 students from SDS Bakau Estate. The technique for determining the sample was by using purposive sampling, taking based on certain objectives as many as 30 students from SDS Mangrove Estate. Data analysis techniques were processed using computer assistance through the SPSS 22.0 program. Based on the data analysis, the results obtained: (1) There is a leg length performance with a 50-meter sprint ability of SDS Bakau Estate students, as evidenced by the value of r arithmetic ( ro ) = 0.382 (0.037 <0.05), (2) There is a weight performance with a 50 sprint ability meters at SDS Bakau Estate students, as evidenced by the value of r arithmetic ( ro ) = 0.409 (0.025<0.05), and (3) there is a performance of leg length and body weight on the 50-meter sprint ability of SDS Bakau Estate, as evidenced by the calculated R-value obtained R = 0.533, R2 value = 0.285 or 36.6% and calculated F value = 5.368 (0.011<0.05).